COMPARISON PROCESS OF SOLVENT-FREE MICROWAVE EXTRACTION AND MICROWAVE HYDRO-DISTILLATION METHODS IN ESSENTIAL OIL PRODUCTION FROM CABBAGE ROSES FLOWER (Rose × centifolia) - Syah Sultan Ali Muzakhar; Lutfi Rizki Fauzi; Ditta Kharisma Yollanda Putri (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2023)
Indonesia has many diverse natural resources that still cannot be utilized optimally such as the extraction of essential oil from Cabbage Roses flowers (Rose × centifolia). This study compares the extraction amendments, extraction time, and essential oil composition of fresh rose flowers obtained by the Solvent-Free Microwave Extraction (SFME) method to those obtained using the Microwave Hydro-Distillation (MHD) extraction method. Optimum conditions using the same amount of raw material in this study for the MHD method optimum conditions of operation: time of 90 minutes; the ratio of 1 g/mL; the power of 450 W, obtained a yield of 0.152% and SFME method optimum conditions of operation: time of 90 minutes, ratio 0.2 g/mL; power 450 W, obtained a yield of 0.358%. Electricity consumption to obtain 1 g of rose essential oil extracted using the MHD method is 4.087 kWh, while for the SFME method, it is 1.073 kWh. So it can also be said that the MHD method requires electricity consumption which is 3.8 times higher when compared to the SFME method.